Boats Depiction in the 8th Century CE Nilotic Frames Mosaic in the Church of St. Stephen, Umm al-Rasas, Jordan - Friedman, Z. (Liber Annuus, 2005)
Abstract Iconography of ships in mosaics comprises two fields, which when put together result in a unique subject, namely ancient ships and shipping, and mosaic making. The vessels depicted within the 8th century Nilotic frame mosaic in the Church of St. Stephen at Umm al-Rasas, Jordan, were not studied yet from the point of view of marine archaeology. These vessels are the subject of the following paper. They were not used as decorative motifs rather they are symbols of similar ancient vessels that sailed in the Nile and the Delta or along the Mediterranean coasts in antiquity.